2018
DOI: 10.2116/analsci.18p058
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Confusable Herbal Medicines by Mapping of Partial Degradation Products from Herbal Medicine Polysaccharides

Abstract: Partial degradation products (PDPs) of herbal medicine (HM) polysaccharides with precolumn derivatization using 1-phenyl-3-methy-5-pyrazolone (PMP) were mapped by high performance liquid chromatography (HPLC), and three groups of confusable HMs were differentiated using the PDP fingerprints assisted with cluster analysis (CA). Three variables of HPLC mobile phase, i.e. acetonitrile proportion, buffer concentration and pH value were optimized with PDP of β-cyclodextrin. Radix Glehniae and Radix Adenophorae; Rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…At the same time, the actual production processes between different manufacturers, equipment models, controlled process parameters, operators, and other factors, result in different product quality. Zhang et al [29] used the CZE method to determine the partial acid degradation products of polysaccharides in fermented Cordyceps powder and found that the CZE fingerprints of partial acid degradation products of polysaccharides from different fermented Cordyceps powder capsules were obviously different. Liu et al [30] established the characteristic fingerprint of monosaccharides in Ginkgo armillaria oral solution based on the precolumn derivation highperformance liquid chromatography method and found that the total degradation fingerprint of G. armillaria oral solution polysaccharide from different manufacturers was obviously different.…”
Section: Determination Of the Characteristic Degradation Fingerprint ...mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the actual production processes between different manufacturers, equipment models, controlled process parameters, operators, and other factors, result in different product quality. Zhang et al [29] used the CZE method to determine the partial acid degradation products of polysaccharides in fermented Cordyceps powder and found that the CZE fingerprints of partial acid degradation products of polysaccharides from different fermented Cordyceps powder capsules were obviously different. Liu et al [30] established the characteristic fingerprint of monosaccharides in Ginkgo armillaria oral solution based on the precolumn derivation highperformance liquid chromatography method and found that the total degradation fingerprint of G. armillaria oral solution polysaccharide from different manufacturers was obviously different.…”
Section: Determination Of the Characteristic Degradation Fingerprint ...mentioning
confidence: 99%
“…The partial degraded products of polysaccharides not only have biological activities but also can reflect the structural characteristics of the original polysaccharides [9]. Based on the characteristics of polysaccharides degradation products, our group has completed the identification of easily mixed medicinal materials such as R. glehniae and R. adenophorae , R. sophorae tokinensis and Rhizoma menispermi , R. achyranthis bidentatae and R. cyathulae , etc [10], which provides a new way for the quality control of TCM. At present, the monosaccharide composition of CBG polysaccharides has been determined to be composed of xylose, arabinose, glucose, rhamnose, mannose, galactose, glucuronic acid, and galacturonic acid in our previous work [11], whereas the study of partial degradation products of CBG polysaccharides has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Confusable herbal medicines are those with similar characteristics, name or mixed clinical prescription but differ because of, for example, different traditional use. To identify such medicines, polysaccharides have been extracted, converted into PMP derivatives and examined by HPLC and MALDI‐quadrupole ion trap (QIT)‐TOF MS (Yang, Guo, et al, 2018).…”
Section: Medical Applicationsmentioning
confidence: 99%